Efektivitas Ruang Terbuka Hijau Publik dalam Menyerap Emisi Karbon Dioksida untuk Mendukung Keberlanjutan Lingkungan Perkotaan - Parid Pakaya; Fitryane Lihawa; Dewi Wahyuni K. Baderan (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
Public Green Open Space (RTH) is an essential element in urban spatial planning to support environmental sustainability. Through the process of photosynthesis, RTH helps absorb carbon dioxide (CO₂) produced by human activities, such as transportation and industry, thus contributing to climate change mitigation. This study aims to explore the role of RTH in absorbing CO₂ and the challenges faced in its management. The study was conducted using a systematic approach through literature analysis and case studies in several cities in Indonesia and around the world. The research results indicate that vegetation type, area size, and environmental conditions are the main factors affecting the carbon absorption capacity of RTH. Large trees have a significantly higher capacity to absorb CO₂ compared to shrubs and grass, with the ability to absorb up to 250.63 tons of CO₂ per year per tree. However, challenges such as limited RTH area, urbanization pressure, and lack of public awareness remain obstacles to optimal RTH management. The recommendations of this study include increasing the area and quality of RTH through data-based strategies, community participation in management, and the development of policies that support sustainability. With proper management, RTH can function as a climate change mitigation tool while improving the quality of life for urban communities.